1971
DOI: 10.1007/bf00564759
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin — A new flavone glycoside of Adonis vernalis

Abstract: The isolation from the epigeal part of Adonis vernalis L. (spring adonis) of a xyloside of homoorientin called adonivernith has been reported in the literature [1]. It was later established [2] that this flavonoid glycoside is a xyloside of orientin and not of homoorientin. Xylosides of orientin [3, 4] and of homoorientin [5] have also been isolated by other workers. We called the xyloside of orientin adonivernith and the xyloside of homoorientin homoadonivernith [6]. Orientin, homoorientin [1], and luteolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Along with the isolated cardiac compounds, many flavones were also identified. Adonivernith (luteolin-8-hexityl monoxyloside) (76), homoadonivernith (77), orientin (78), homoorientin (79), isoorientin (80), luteolin (81) and vitexin (82) were isolated from A. vernalis (Chernobai et al, 1968; Drozd et al, 1971; Wagner et al, 1975; Budzianowski et al, 1991), and adonivernith also was found in A. leiosepala (Evdokimov, 1979).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Along with the isolated cardiac compounds, many flavones were also identified. Adonivernith (luteolin-8-hexityl monoxyloside) (76), homoadonivernith (77), orientin (78), homoorientin (79), isoorientin (80), luteolin (81) and vitexin (82) were isolated from A. vernalis (Chernobai et al, 1968; Drozd et al, 1971; Wagner et al, 1975; Budzianowski et al, 1991), and adonivernith also was found in A. leiosepala (Evdokimov, 1979).…”
Section: Phytochemistrymentioning
confidence: 99%